The correlation between serum magnesium level and blood pressure in patient with chronic kidney disease - Maulida Devi Yanti; Lisyani Budipradigdo Suromo (DiscoverSys Inc., 2019)
Background: Increased blood pressure is one of the complications from hemodialysis in Chronic Kidney Disease (CKD) patients. Magnesium is an electrolyte which is a calcium antagonist in regulating blood pressure. This study aims to prove the correlation of serum magnesium level with blood pressure in CKD patientsMethods: A cross-sectional study was conducted on 30 CKD patients in Dr. Kariadi Hospital, Semarang during September–October 2018. The serum magnesium level was measured with spectrophotometry method, blood pressure with a sphygmomanometer. Statistical analysis used Pearson and Spearman correlation test.Result: There is a significant correlation between serum magnesium level and systolic blood pressure with p< 0,001 and r=-0,737 and correlation between serum magnesium level and diastolic blood pressure with p=0,011 and r=-0,457Conclusion: There is a strong negative correlation of serum magnesium level with systolic blood pressure and moderate negative correlation of serum magnesium level with diastolic blood pressure in this study. Further studies are needed to analyze the influential factors of blood pressure.